Capital Structure as a Bargaining Tool: The Role of Leverage in Contract Renegotiation - Perotti, Enrico C.; Spier, Kathryn E. (American Economic Review, 1993)
This paper presents a strategic model of temporarily high leverage. When the repayment of senior claims depends in part upon further investment, shareholders may be able to alter credibly their incentives to invest through an exchange of junior debt for equity and thereby force concessions from senior creditors. We focus on the conflict between shareholders and risk-averse workers and show that this strategic use of debt leads to an inefficient allocation of risk. We characterize conditions under which firms will undergo leveraged recapitalizations, their choice of debt instruments, and the dynamics of their capital structure.